Pattern of Corneal Diseases in Paediatric Age Group at a Tertiary Eye Care Center in Nepal - Shah, A; Chaudhary, M; Shrestha, J K (Nepalese Journal of Ophthalmology, 2017)
Objective: It is to study the pattern of corneal diseases (including injuries) in paediatric population in a tertiary eye care center. Materials and methods: A descriptive, cross sectional study was carried out in a tertiary eye care center which included 176 cases. Results: Out of 176 cases studied, 6 cases (3.4%) presented with congenital causes, 4 cases (2.27%) were of dystrophy and ectasia, 63 cases (35.79%) had infective origin, 17 cases (9.65%) had inflammatory cause, 9 cases (5.11%) had systemic association and 77 cases (43.75%) had traumatic causes. Conclusion: Trauma was noted to be the most important cause for corneal diseases in paediatric population followed by infective conditions. Viral keratitis was found to be the most common type of corneal infection in the paediatric age group.